Gandhi – of the earth, earthy: A Critical View of Gandhi in South Africa. Issue 1 (2nd January 2017) - Govinden, Betty
Abstract : It is clear that the last word has not been written on Gandhi, nor is it likely to be in the future. A multitude of scholars – from India and South Africa, and from other parts of the world – have produced studies on Gandhi, and the corpus extends to a wide spectrum, from the variously hagiographical or informative, to the critical and contentious. In this article, I consider the particular criticism of Gandhi in relation to his attitude and relationships with Africans. I argue that Gandhi must be seen in the context of the highly fraught politics of the colonial frontier in Natal, and the wider ambiguities, of the period during which he was is South Africa.